Exponential stability and Exponential synchronization results for fractional order impulsive Neural Networks (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper we focus on exponential stability analysis of Caputo fractional order impulsive neural network using convex Lyapunov function and obtain the suitable LMI conditions. We have also included exponential synchronization of error system that is derived from the drive-response system. The obtained results are verified using examples.